Argyrophilic Grain Disease: Demographics, Clinical, and Neuropathological Features From a Large Autopsy Study. Issue 7 (July 2016) - Rodriguez, Roberta Diehl; Suemoto, Claudia Kimie; Molina, Mariana; Nascimento, Camila Fernandes; Leite, Renata Elaine Paraizo; de Lucena Ferretti-Rebustini, Renata Eloah; Farfel, José Marcelo; Heinsen, Helmut; Nitrini, Ricardo; Ueda, Kenji; Pasqualucci, Carlos Augusto; Jacob-Filho, Wilson; et al.
Abstract : Argyrophilic grain disease (AGD) is a frequent late-onset, 4-repeat tauopathy reported in Caucasians with high educational attainment. Little is known about AGD in non-Caucasians or in those with low educational attainment. We describe AGD demographics, clinical, and neuropathological features in a multiethnic cohort of 983 subjects ≥50 years of age from São Paulo, Brazil. Clinical data were collected through semistructured interviews with an informant and included in the Informant Questionnaire on Cognitive Decline in the Elderly, the Clinical Dementia Rating, and the Neuropsychiatric Inventory. Neuropathologic assessment relied on internationally accepted criteria. AGD was frequent (15.2%) and was the only neuropathological diagnosis in 8.9% of all cases (mean, 78.9 ± 9.4 years); it rarely occurred as an isolated neuropathological finding. AGD was associated with older age, lower socioeconomic status (SES), and appetite disorders. This is the first study of demographic, clinical, and neuropathological aspects of AGD in different ethnicities and subjects from all socioeconomic strata. The results suggest that prospective studies of AGD patients include levels of hormones related to appetite control as possible antemortem markers. Moreover, understanding the mechanisms behind higher susceptibility to AGD of low SES subjects may disclose novel environmental risk factors for AGD and other neurodegenerative diseases.